New pyrene and fluorene-based π-conjugated Schiff bases: Theoretical and experimental investigation of optical properties - Sivrikaya Yunuscan; Can Sakarya Handan; Kiliç Gökhan; Ekti Sultan Funda; Yandimoğlu Merve (Journal of the Serbian Chemical Society, 2024)
The new Schiff bases with D-π-A system were synthesized by the reaction of polycyclic aldehydes and substituted benzothiazoles. The structures of the synthesized Schiff bases (7a and 9a) were determined by FT-IR, 1H- -NMR, 13C-NMR, ESI-Mass and elemental analyses. The optical properties of the new compounds were investigated and the optical band gaps (Eg) were calculated by the Tauc method using the UV–Vis absorption spectra. Density functional theory (DFT/B3LYP/6-31G(d,p)) calculations were conducted to get more insight on the structural and electronic properties of novel Schiff bases. The optimized molecular geometry, UV–Vis spectroscopic parameters and HOMO–LUMO energies were examined and the calculated results were compared with experimental data.